Motion management during IMAT treatment of mobile lung tumors—A comparison of MLC tracking and gated delivery. Issue 10 (24th September 2014) - Falk, Marianne; Pommer, Tobias; Keall, Paul; Korreman, Stine; Persson, Gitte; Poulsen, Per; Munck af Rosenschöld, Per
Abstract : Purpose: : To compare real‐time dynamic multileaf collimator (MLC) tracking, respiratory amplitude and phase gating, and no compensation for intrafraction motion management during intensity modulated arc therapy (IMAT). Methods: : Motion management with MLC tracking and gating was evaluated for four lung cancer patients. The IMAT plans were delivered to a dosimetric phantom mounted onto a 3D motion phantom performing patient‐specific lung tumor motion. The MLC tracking system was guided by an optical system that used stereoscopic infrared (IR) cameras and five spherical reflecting markers attached to the dosimetric phantom. The gated delivery used a duty cycle of 35% and collected position data using an IR camera and two reflecting markers attached to a marker block. Results: : The average gamma index failure rate (2% and 2 mm criteria) was <0.01% with amplitude gating for all patients, and <0.1% with phase gating and <3.7% with MLC tracking for three of the four patients. One of the patients had an average failure rate of 15.1% with phase gating and 18.3% with MLC tracking. With no motion compensation, the average gamma index failure rate ranged from 7.1% to 46.9% for the different patients. Evaluation of the dosimetric error contributions showed that the gated delivery mainly had errors in target localization, while MLC tracking also had contributions from MLC leaf fitting and leaf adjustment. The average treatment time was about three times longer with gating compared to delivery with MLC tracking (that did not prolong the treatment time) or no motion compensation. For two of the patients, the different motion compensation techniques allowed for approximately the same margin reduction but for two of the patients, gating enabled a larger reduction of the margins than MLC tracking. Conclusions: : Both gating and MLC tracking reduced the effects of the target movements, although the gated delivery showed a better dosimetric accuracy and enabled a larger reduction of the margins in some cases. MLC tracking did not prolong the treatment time compared to delivery with no motion compensation while gating had a considerably longer delivery time. In a clinical setting, the optical monitoring of the patients breathing would have to be correlated to the internal movements of the tumor.